Who is government? : the untold story of public service - Lewis, Michael (Michael M.); Cep, Casey N.; Eggers, Dave; Lanchester, John; Brooks, Geraldine; Vowell, Sarah, 1969-; Bell, W. Kamau (Riverhead Books, 2025)
"The government is a vast, complex system that Americans pay for, rebel against, rely upon, dismiss, and celebrate. It's also our shared resource for addressing the biggest problems of society. And it's made up of people, mostly unrecognized and uncelebrated, doing work that can be deeply consequential and beneficial to everyone. Michael Lewis invited his favorite writers to find someone doing an interesting job for the government and write about them in a special in-depth series for the Washington Post. The stories they found are unexpected, riveting, and inspiring, including a former coal miner devoted to making mine roofs less likely to collapse, saving thousands of lives; an IRS agent straight out of a crime thriller; and the manager who made the National Cemetery Administration the best-run organization, public or private, in the entire country. Each essay shines a spotlight on the essential behind-the-scenes work of exemplary federal employees. Whether they're digitizing archives, chasing down cybercriminals, or discovering new planets, these public servants are committed to their work and universally reluctant to take credit. Expanding on the Washington Post series, the vivid profiles in Who Is Government? blow up the stereotype of the irrelevant bureaucrat. They show how the essential business of government makes our lives possible, and how much it matters"--